2000
DOI: 10.1110/ps.9.8.1567
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional consequences of removal of the interdomain disulfide bridge from the isolated C‐lobe of ovotransferrin

Abstract: The interdomain disulfide bond present in the C-lobe of all the transferrins was postulated to restrict the domain movement resulting in the slow rate of iron uptake and release. In the present study, the conformational stability and iron binding properties of a derivative of the isolated C-lobe of ovotransferrin in which the interdomain disulfide bond, Cys478-Cys671 was selectively reduced and alkylated with iodoacetamide were compared with the disulfide intact form at the endosomal pH of 5.6. Pyrophosphate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Other studies have shown that selective reduction of disulphide bonds is possible with limited use of DTT. 24 We found that 1 mmol/L DTT was sufficient to selectively reduce the Cys 264 -Cys 395 disulphide bond without compromising the conformational state of the kringle 2 module, as evidenced by the fact that K2 was still able to bind lysine-Sepharose after DTT treatment. Human and mouse endothelial cell migration was significantly reduced in a scratch wound assay after treatment with K2 containing tPA fragments, as was in vivo angiogenesis in a mouse sponge angiogenesis assay.…”
Section: Discussionmentioning
confidence: 79%
“…Other studies have shown that selective reduction of disulphide bonds is possible with limited use of DTT. 24 We found that 1 mmol/L DTT was sufficient to selectively reduce the Cys 264 -Cys 395 disulphide bond without compromising the conformational state of the kringle 2 module, as evidenced by the fact that K2 was still able to bind lysine-Sepharose after DTT treatment. Human and mouse endothelial cell migration was significantly reduced in a scratch wound assay after treatment with K2 containing tPA fragments, as was in vivo angiogenesis in a mouse sponge angiogenesis assay.…”
Section: Discussionmentioning
confidence: 79%
“…OTf has a broad-spectrum antibacterial ability, mainly due to its binding capability to the iron ions which is necessary for microbial growth. 49 It has been confirmed that phosphorylated OTf significantly enhanced antibacterial activity against Escherichia coli, Staphylococcus aureus, and Bacillus subtilis. 50 Thus, we can speculate that the increased phosphorylation of Tyr 191 might promote the antibacterial ability of egg white and yolk, which in turn protect chicken embryo from bacterial infections.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 89%
“…26 Except for a few cases, 39 it has been generally reported that disulfide bonds are responsible for a stabilization of the overall three-dimensional structure of proteins of different sizes, regardless of their structural organization. [40][41][42][43][44][45][46][47] It is clear that the native disulfide bond of EcoAcP also has a marked influence on the folding process of this protein. EcoAcP exhibits two-state refolding across the whole range of denaturant concentrations studied, with no early folding event within the dead time of the instrument (Fig.…”
Section: Discussionmentioning
confidence: 99%